2014
DOI: 10.1021/ie404089t
|View full text |Cite
|
Sign up to set email alerts
|

Flame Retardancy of Polyester and Polyester–Cotton Blends Treated with Caseins

Abstract: For the first time, polyester and polyester−cotton fabrics have been treated with an aqueous suspension of caseins to increase their thermal stability and flame retardancy. The effectiveness of the fabric treatment as well as the morphology of the deposited coatings have been assessed by infrared spectroscopy and scanning electron microscopy, respectively. The thermal stability of the treated fabrics in nitrogen and air, as well as their resistance to a flame application and to an irradiative heat flux of 35 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(70 citation statements)
references
References 21 publications
1
68
0
1
Order By: Relevance
“…In this regard, it is worth mentioning that a recent study has reported a realisation of 10.5 g inorganic salts from the evaporation of 500 ml of aqueous ash extract collected by burning the air-dried banana pseudostem. The researchers have also reported that potassium chloride, sodium chloride and metal phosphate are the major composition of that salt 13 , and magnesium nitrate and potassium nitrate are the two major active components present in the BPS as confi rmed by GC-MS analysis, and those can also act as fi re retardant 15 . In the present study, the BPS has helped the cotton textile not only to be fl ame retardant, but also to form some sort of complex groups with the mordants that might have also aided the sample to be better fl ame retardant, resulting in high uptake of the BPS in the pre-mordanted fabric.…”
Section: Mechanism Of Imparting Fl Ame Retardant Propertymentioning
confidence: 93%
“…In this regard, it is worth mentioning that a recent study has reported a realisation of 10.5 g inorganic salts from the evaporation of 500 ml of aqueous ash extract collected by burning the air-dried banana pseudostem. The researchers have also reported that potassium chloride, sodium chloride and metal phosphate are the major composition of that salt 13 , and magnesium nitrate and potassium nitrate are the two major active components present in the BPS as confi rmed by GC-MS analysis, and those can also act as fi re retardant 15 . In the present study, the BPS has helped the cotton textile not only to be fl ame retardant, but also to form some sort of complex groups with the mordants that might have also aided the sample to be better fl ame retardant, resulting in high uptake of the BPS in the pre-mordanted fabric.…”
Section: Mechanism Of Imparting Fl Ame Retardant Propertymentioning
confidence: 93%
“…In case of CO/PET fabrics, the following observations were detected; all samples showed two independent stages of thermal decomposition, the first stage (at lower temperature) is due to the CO fiber degradation while the later stage (at higher temperature) is due to the decomposition of polyester fiber [1,22]. Also, T max1 and T o1 values decrease as HBPU concentration increases during treatment process.…”
Section: °Cmentioning
confidence: 85%
“…Recently, researchers reported that DNA from herring sperm and solomon fishes can be applied to cotton fabric to make it thermally stable . Attempts have also been made to make cotton fabrics fire retardant using whey proteins, casein and hydrophobins due to their phosphate, disulphide and protein content, as they can influence pyrolysis by early char formation . Recently researchers have used chicken feather protein with a combination of borax and boric acid to make woven cotton fabric fire retardant .…”
Section: Introductionmentioning
confidence: 99%